Analisis Kategori Kelas Kata Pada Cerita Rakyat “Sitagan Bulu” Yang Berasal Dari Batak Toba - Simaremare, Juni Agus; Padang, Sepmasrina; Sinaga, Amelia K.D.; Sagala, Novita E. (Asosiasi dosen IDEBAHASA KEPRI, 2023)
This research aims to determine the categories of word classes contained in the Si Tugan Bulu folklore from the Toba Batak region. In the linguistic dictionary, the definition of morphology is the field of linguistics that studies morphemes and their combinations or parts of language structure which include words and parts of words, namely morphemes. This research used theory of morphemes as discussed by Chaer (2012) where a linguistic concept focusing on the smallest grammatical units in a language. Morphemes carry meaning and function as the foundation of morphology, shaping words and their structures.The method used in this research is the library research method. The results and research of this and the word class categories in the short story